ANALYSIS AND INTERPRETATION OF REGIONAL-SCALED GRAVITY MEASUREMENTS IN THE CENTRAL EQUATORIAL ATLANTIC REGION OF AFRICA - Oluwatimilehin B. Balogun; Olajumoke C. Akintokewa (Rudarsko-geološko-naftni Zbornik, 2020)
Regional-scaled gravity data was interpreted for the Central Equatorial Atlantic African region, a region comprising of both oceanic and continental areas, with a view to understanding more about its complex geological settings and the processes of tectonic evolution. The methods adopted involved the generation of topography/bathymetry, free-air and Bouguer anomaly grids from topography, free-air anomaly and Bouguer anomaly datasets; regional-residual gravity field separation, lineament mapping from the Horizontal Derivative and 2-D modelling of the sub-surface. Within the study area, the elevation ranged from -4,200 to 3,840 m. The free-air anomaly map showed a combination of elongated and circular positive free-air anomalies and elongated, negative free-air anomalies whose values varied between -40 mGal and 70 mGal. The Bouguer anomaly values ranged from -121 to +229 mGal. The Bouguer anomaly map also showed both elongated and circular positive and negative Bouguer anomalies. The dominant orientations of the elongated Bouguer anomalies were the NE-SW, the E-W and the ESE-WNW orientations. Gravity modelling within the oceanic region revealed the presence of a basaltic cover whose thickness varied between 1,330 m to 7,700 m in the oceanic and continental margin regions. Associated with the occurrence of this basaltic cover were kinks interpreted as eruption fissures from which the basaltic cover was ejected. It was discovered that the African West Coast Atlantic margin consisted of a trench around the continental margin region adjoined just to the north by some high density basalt, and also that the West African Coastline is heavily laced with magmatism and must have therefore been an active magmatic region in the past. Based on the interpreted data, the study concluded that the Equatorial Atlantic Ocean might have opened on a framework of rifts which extended into the inland regions to form the present day sedimentary basins and from the Bouguer anomaly profile along latitude 10oN that it is possible that both the Minna batholith and the Jos Plateau exploited the Proterozoic basement weaknesses for their emplacement.